The evolution of crystal fabric in ice sheets and its link to climate history - Kennedy, Joseph H. (2013)
The evolution of preferred crystal-orientation fabrics is strongly sensitive to the initial fabric and texture. A perturbation in climate can induce variations in fabric and texture in the firn. Feedbacks between fabric evolution and ice deformation can enhance these variations through time and depth in an ice sheet. We model the evolution of fabric under vertical uniaxial-compression and pureshear regimes typical of ice divides. Using an analytic anisotropic flow law applied to an aggregate of distinct ice crystals, the model evolves the fabric and includes parameterizations of crystal growth, polygonization and migration recrystallization. Stress and temperature history drive the fabric evolution. Using this model, we explore the evolution of a subtle variation in near-surface fabric using both constant applied stress and a stress–temperature history based on data from Taylor Dome, East Antarctica. Our model suggests that a subtle variation in fabric caused by climate perturbations will be preserved through time and depth in an ice sheet. The stress history and polygonization rate primarily control the magnitude of the preserved climate signal. These results offer the possibility of extracting information about past climate directly from ice fabrics.